Policies and actors in the agriculture innovation system - Adinolfi F.; Di Pasquale J. (Innovation in the Mediterranean agrifood sector. Concepts, experiences and actors in a developing ecosystem, 2016)
There is a long tradition of State intervention to support agriculture, and this has to do as much with national security issues (food security) as with the need to respond to market failures caused by the specificities of agricultural systems, especially in very recent times. The justification for public action aimed at supporting the innovation system in agriculture is that the results and implications of agricultural research are often a “public asset”, that the actors in the agrifood system - particularly those in the primary sector – are often fragmented, and that long time lapses frequently occur between the creation of an innovation and its adoption. Nowadays, active involvement of the final users of innovation is the key point, and this contributes to definitively overturning the view of agricultural innovation as a “supply driven” process. The chapter documents this transition at the European level, as reflected in the tools provided by the agricultural innovation policies. Within the initiatives promoted for the 2014-2020 programming period, it mentions the European Innovation Partnerships (EIPs) as the tool that most favours the new approach.